Virtual System Control Using Hand Gestures - R Sanjay, M Karthiga, P Geetha, S Sanjay Koushik, B Rahul Siddarth (Mathematical Statistician and Engineering Applications, 2023)
As the technologies are developing day by day the devices are gradually becoming compact in size. Some devices have gone wireless, some of them gone latent. This project proposes a system that could make some of the devices go latent which is the future of HCI (Human-Computer Interaction). Our paper deals with controlling the cursor pointer with the bare hands using hand gestures without using any electronic device either wired or wireless. The operations of mouse like left click, right click, cursor pointer movement, scroll up and scroll down functions will be manipulated and processed using bare hands different gestures.This project advances a methodology for the next generation of Human Computer Interaction (HCI) in which the system can be taken into control by using mouse cursor movement which in turn will be controlled by making use of a live camera using hand gestures. The methodology we have presented is an advancement to the present strategy which includes wired mouse and wireless input devices like mouse and keyboard. Our system with the help of computer vision technology makes use of a camera to take control of the system using mouse events and is apt for performing tasks that a physical computer mouse can do. This system will get into control of the user with the help of their hand gestures by manipulating real-time images from the live stream, where the frames will be processed for gesture mapping in pattern finding. It’s an immediate process and the cursor in the desktop will immediately move.